Crystal Coconut Sugar: Health Benefits and Market Potential - Zuhair, Muhammad Arianda Fairuz; Al-Umarajati, Rasikhah; Mardatillah, Mardatillah; Pebrianti, Lia; Rania, Khansa Putri; Valyanto, Meriel Khansa; Aini, Nur (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2024)
Crystal coconut sugar is a natural sweetener made from coconut sap through a heating and crystallization process resulting in fine-texturized sugar granules. This sugar has a low glycemic index ranging from 35 to 44, making it a healthier alternative to granulated sugar. The nutritional content of crystal coconut sugar, including minerals, vitamin B and C, and antioxidants, provides various health benefits. These benefits include maintaining the body’s electrolyte balance, strengthening the immune system, preventing anemia, and supporting energy metabolism. The low glycemic index makes crystal coconut sugar safe for diabetics, as it does not cause sharp spikes in blood sugar levels. The demand for crystal coconut sugar is rising due to the influence of healthy lifestyles and increased awareness of environmentally friendly products. Indonesia holds significant potential to become a leading supplier of crystal coconut sugar in the global market. The crystal coconut sugar industry in Banyumas Regency, Central Java, has evolved into a thriving export commodity with a substantial market share. This highlights the promising opportunities for crystal coconut sugar as a key export product.